Irradiation with 310 nm and 340 nm ultraviolet light-emitting-diodes can improve atopic dermatitis-like skin lesions in NC/Nga mice. Issue 8 (18th July 2018) - Kwon, Tae-Rin; Kim, Jong Hwan; Hong, Ji-Yeon; Seok, Joon; Kim, Jae Min; Bak, Dong-Ho; Choi, Mi-Ji; Mun, Seok Kyun; Kim, Chan Woong; Kim, Beom Joon
Abstract : Ultraviolet (UV) light produces an immunomodulatory effect on the skin and is widely used for the treatment of chronic inflammatory skin diseases. Abstract : Ultraviolet (UV) light produces an immunomodulatory effect on the skin and is widely used for the treatment of chronic inflammatory skin diseases. UV light emitting diodes (UV-LEDs) are a new and promising source of UV radiation. However, their mechanism of action remains largely unknown. In this study, we tested the safety and effectiveness of UV-LED irradiation for the treatment of atopic dermatitis (AD) in an NC/Nga mouse model. Mice were divided into seven groups of eight mice each. Application of Dermatophagoides farinae (Df) extract ointment for four weeks induced AD-like skin lesions. Subsequently, the mice were exposed to UV-LEDs, narrow band UVB, or UVA irradiation three times per week. We assessed the immunosuppressive effects of 310 nm (50 mJ cm −2 ) and 340 nm (5 J cm −2 ) UV-LED irradiation. Histological analyses using hematoxylin–eosin, toluidine blue, and immunohistochemical staining were performed. In addition, the serum levels of IgE, inflammatory cytokines and chemokines were measured using enzyme-linked immunosorbent assays (ELISAs). UV-LED irradiation significantly alleviated AD-like skin symptoms, including edema, erythema, dryness, and itching, by modulating Th1 and Th2 responses, transepidermal water loss (TEWL), and scratching behavior in NC/Nga mice. These results suggest that UV-LEDs can improve the treatment of inflammatory skin diseases.